Measurements of Tropospheric Bromine Monoxide Over Four Halogen Activation Seasons in the Canadian High Arctic. Issue 18 (16th September 2020) - Bognar, K.; Zhao, X.; Strong, K.; Chang, R. Y.‐W.; Frieß, U.; Hayes, P. L.; McClure‐Begley, A.; Morris, S.; Tremblay, S.; Vicente‐Luis, A.
Abstract: Bromine explosions and corresponding ozone depletion events are common in the Arctic spring. The snowpack on sea ice and sea salt aerosols (SSA) are both thought to release bromine, but the relative contribution of each source is not yet known. Furthermore, the role of atmospheric conditions is not fully understood. Long‐term measurements of bromine monoxide (BrO) provide useful insight into the underlying processes of bromine activation. Here we present a 4‐year data set (2016–2019) of springtime BrO partial columns retrieved from Multi‐AXis Differential Optical Absorption Spectroscopy (MAX‐DOAS) measurements in Eureka, Canada (80.1°N, 86.4°W, 610 m asl). Due to the elevation of the measurement site, the instrument often measures BrO in the free troposphere, except during strong wind episodes and storms that generate a deep boundary layer. Enhanced vertical mixing due to strong winds leads to increasing BrO values and reduced ozone depletion. We find that BrO enhancements show two modes differentiated by local wind direction and air mass history. Longer time spent by the airmass in first‐year sea ice areas corresponds to increased BrO for one of these modes only. Furthermore, we argue that snow on multiyear ice might also contribute to bromine release. High aerosol optical depth is required to maintain lofted BrO, and we show that the presence of coarse‐mode aerosols (>0.5 μm, likely SSA) is a necessary and sufficient condition for observing BrO at our elevated measurement site in Eureka. This work highlights the importance of considering variable local conditions when characterizing bromine activation. Key Points: High wind speeds lead to enhanced tropospheric BrO with little to no ozone depletion Snow on first‐year ice and multiyear ice likely both contribute to observed BrO enhancements High coarse‐mode (>0.5 μm) aerosol load is necessary and sufficient to maintain enhanced BrO aloft